Efektivitas Program Indonesia Pintar terhadap Partisipasi Sekolah di Kawasan Barat dan Timur Indonesia - Mulyani, Fitri; Ridwan, Endrizal; Nazer, M. (Jurnal Informatika Ekonomi Bisnis, 2023)
Smart Indonesia Program (PIP) is a government program that aims to make the 12-year compulsory education program a success. The PIP program has been running since 2015. However, the Badan Pusat Statistik (BPS) notes that there are still school-age residents who are not attending school, even though the percentage of children not attending school has decreased. This study aims to measure the implementation of PIP and other factors on school participation in two regions, namely the West Indonesia Region (KBI) and the East Indonesia Region (KTI) in 2021. This research uses data from the 2021 National Socio-Economic Survey (Susenas) in the Indonesian Region West (KBI) and Eastern Indonesia Region (KTI). Data analysis used logistic regression method. The results showed that all independent variables, PIP, gender, marital status of head of household, classification of area of residence, per capita expenditure, other social assistance had a significant effect on school enrollment in the Western Regions of Indonesia (KBI) and Eastern Indonesia (KTI). . The biggest tendency for children to participate in school is the PIP.